Role of hypoxic pulmonary vasoconstriction in pulmonary gas exchange and blood flow distribution. 2. Pathophysiology - Marshall, B E; Hanson, C W; Frasch, F; Marshall, C (Intensive care medicine, 1994)
In this review, the second of a two part series, the analytic techniques introduced in the first part are applied to a broad range of pulmonary pathophysiologic conditions. The contributions of hypoxic pulmonary vasoconstriction to both homeostasis and pathophysiology are quantitated for atelectasis, pneumonia, sepsis, pulmonary embolism, chronic obstructive pulmonary disease and adult respiratory distress syndrome. For each disease state the influence of principle variables, including inspired oxygen concentration, cardiac output and severity of pathology are explored and the actions of selected drugs including inhaled nitric oxide and infused vasodilators are illustrated. It is concluded that hypoxic pulmonary vasoconstriction is often a critical determinant of hypoxemia and/or pulmonary hypertension. Furthermore this analysis demonstrates the value of computer simulation to reveal which of the many variables are most responsible for pathophysiologic results.